Hidroksida Berlapis Ganda ZnCrCI: Kesan Haba Terhadap Luas Perm.ukaan dan Keliangan - Hussien, Mohd Zobir; Zainal, Zulkarnain; Ibrahim, Ramli; Hii, Hiong Swee (Universiti Putra Malaysia Press, 1996)
ZnCrCI layered double hydroxides, with Zn/Cr ratios (R) 3 and 4 were prepared by a coprecipitation method and heat treated samples were subsequently prepared. Their bulk structure was investigated by X-ray diffraction and surface area techniques. X-ray diffraction analysis showed that the layered double hydroxide phase remained unchanged upon heating up to 250°C for 5 h in an oven at atmospheric pressure. However, new phases, namely spinel-like and ZnO phases appeared when the samples were heated at 350°C and above for the same duration. The specific surface areas decreased with increasing temperature (between 450850° C) for both R values but no trend was observed for temperatures between 250-350°C. Average pore diameter was found to be optimum at 550°C and 450°C for R = 3 and 4, respectively.